NEGATIVISM OF THE CADET YOUTH AS A SOCIAL-PSYCHOLOGICAL PHENOMENON - Kravchenko, K.; Skriabin, O.; Sokolina, O.; Zarytska, A. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
The article presents the results of the empirical research of the phenomenon of negativism among the cadet youth. The research has been carried out on the basis of one of the higher educational institutions of the Armed Forces of Ukraine with the involvement of 239 cadets of different specialties from the 1 till the 5-th year of study. In the course of empirical research, the following methods have been used: testing and content-analyses. The method of the content-analyses has allowed to reaffirm the existing problem once more, whilst the method of testing to determine the social-psychological determinants for the appearance of this phenomenon. Among the methodologies that have been used in terms of research the following have been used: The methodology for determining of the type of personality (J. Oldkham, L. Morris; the short oriented test (V. Busina, E. Vanderlik), designed to determine the level of intellectual capacities; the scale of basic convictions – a methodology aimed at determining the global, permanent beliefs of the individual about the world and himself, the basic beliefs happen to influence the process of thinking, emotional states and the behavior of the individual; the methodology of studying the accents of the personality (K. Leongard, C. Schmischek). Upon the results of the conducted research the following conclusions have been made. The problem of negativism of the cadet youth does not only influence the quality of internal communication and the educational process, but also happens to have the more significant consequences for the Armed Forces of Ukraine as such. Among the main manifestations of negativism in the cadet environment is the attitude towards the educational process, the military educational institution and the officers that are ensuring the process of their training at the higher military educational institution, the military educational unit of the institution of higher education.
Keywords: negativism, sotial-psychological features of cadets, educational process, Armed forces of Ukraine